SISTEM PENDUKUNG KEPUTUSAN PENENTUAN NILAI KENAIKAN PANGKAT TNI ANGKATAN DARAT MENGGUNAKAN METODE COMPOSITE PERFORMANCE INDEX (CPI) - Nugroho, Adam Hasbi; Bahtiar, Nurdin (MATEMATIKA, 2016)
Rank promotion is a part ofpreparationunits in the implementation management of Main Functionwhich is one of the functions that organized by Puspenerbad (Army Aviation Center) in performing the basic tasks of the Army. Rank is required to assist in supporting the placement decisions of the assessment team of Puspenerbad in supporting the decision of placement task or filling vacant positions as officials had previously been moved or changed their title.Therefore, rank promotionneeds to be calculated, computerize, and ranked using a Decision Support Systems (DSS). Decision support systems can helpthe assessment team of Puspenerbad indetermining members that passed or not pass and determine the pass members ranking to get a rank promotion. One method that can be used to help support decisions for determining the value of the Army's promotion is Composite Performance Index (CPI) method. Composite Performance Index (CPI) is one method of calculation of the index-based decision making combined performance that can be used to determine the ratings or rankings of various alternatives based on several criteria, although the criteria vary. Based on the results of comparative testing of samples manually, the accuracy of the CPI method can be considered good.